Determining future high speed rail review topics through bibliometric analysis - Steele, Heather; Blumenfeld, Marcelo; Plummer, Paul (High-speed Railway, 2024)
As High Speed Rail (HSR) has proliferated globally, so has a related research field dedicated to exploring and addressing its unique issues. Yet, studies to understand and classify the HSR research domain are limited. This paper addresses the gap, using bibliometric analysis to identify future research areas and 20 candidate topics for literature review based on keyword analysis through VOSviewer. Article and review papers related to HSR published in the last 20 years (2003–2022) were retrieved from Scopus, and then analyzed to determine the split in knowledge between languages, the collaboration between countries and institutions, highly productive and cited journals, and research topics which have and have not been reviewed. Approximately 30% of the search results were published exclusively in Chinese, highlighting the importance of extending the evaluation to cover both languages. This is a novel aspect of the work, which has enabled the recognition of potential knowledge gaps. It is recommended that future reviews incorporate works in both languages, possibly through international collaboration. Institutions in China and other countries that are strong collaborators have been identified, as well as relevant, highly cited journals.